Development of E-Tourism System for the Bangka Islands Using the Extreme Programming Method Towards Digital Tourism - Zaliman, Iski; Arkan, Fardhan; Anggita, Wenni; Tou, Nurhaeka; Ilmatus Sakdiyah, Nanda Aulia; Wafiqoh, Risnina; Endraswari, Putri Mentari (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2026)
Regional tourism often faces obstacles in providing fast, accurate, and easily accessible destination information to tourists. Many regions lack a digital platform capable of presenting information in an integrated manner, making it difficult for tourists to obtain an overview of tourist attractions, supporting facilities, and travel routes. This information accessibility problem affects the efficiency of tourism promotion and results in suboptimal implementation of digital transformation concepts. This study aims to develop and evaluate a E- Tourism application to improve the accessibility of tourism destination information and support digital transformation in the regional tourism sector. The system development was carried out using the Extreme Programming (XP) approach to ensure a fast iterative process, flexibility to respond to changing user needs, and software quality improvement in each testing cycle. Usability evaluation was conducted using the System Usability Scale (SUS) method involving 70 general user respondents. The test results show that the application obtained a SUS score of 75.74 in the acceptable category, indicating that the application is easy to use, clear, and aligned with tourism information needs.